Molecular change of dissolved organic matter and patterns of bacterial activity in a stream along a land-use gradient. (1st November 2019) - Kamjunke, Norbert; Hertkorn, Norbert; Harir, Mourad; Schmitt-Kopplin, Philippe; Griebler, Christian; Brauns, Mario; von Tümpling, Wolf; Weitere, Markus; Herzsprung, Peter
Abstract: Fluvial networks are globally relevant for the processing of dissolved organic matter (DOM). To investigate the change in molecular DOM diversity along the river course, high-field FTICR mass spectrometry and NMR spectroscopy of riverine DOM as well as bacterial abundance and activity were measured in a third order stream along a land-use gradient from pristine, agricultural to urban landscapes. DOM composition showed a clear evolution along the river course with an initial decrease of average oxidation and unsaturation followed by an increased relative abundance of CHNO and CHOS compounds introduced by agriculture and waste water, respectively. DOM composition was dominated by rather unsaturated CHO compounds (H/C ≤ 1) in headwaters and by more aliphatic molecules at downstream sites. Oxygenated functional groups shifted from aromatic ethers and hydroxyl groups to aliphatic carboxylic acids and aliphatic hydroxyl groups. This massive dislocation of oxygen significantly increased the diversity of atomic environments in branched aliphatic groups from headwater to downstream DOM. Mass spectra of DOM enabled the detection of compositional relationships to bacterial abundance and activity which was positively related to more aliphatic components (H/C > 1) and negatively related to unsaturated components. FTICR mass and NMR spectra corroborated the initial decline in DOM molecular diversity predicted by the River Continuum Concept (RCC) but demonstrated an anthropogenic increase in the molecular diversity of DOM further downstream. While the high DOM molecular diversity in first order headwater streams was the result of small scale ecosystem plurality, agriculture and waste water treatment introduced many components in the lower reaches. These anthropogenic influences together with massive bacterial oxidation of DOM contributed to a growth of molecular diversity of downstream DOM whose composition and structure differed entirely from those found in pristine headwaters. Graphical abstract: Image 1 Highlights: DOM composition evolved from unsaturated to more aliphatic components. Proportions of CHNO and CHOS compounds increased downstream. Bacterial activity was positively related to more aliphatic components. DOM diversity decreased in the upper part (river continuum concept). DOM diversity increased in the lower part with agriculture and urban areas.